The role of religiosity, ethnicity, individual values and innovativeness in consumer acceptance of novel products - Mansori, Shaheen (2012)
Traditional marketing strategies have been inexorably changed by the new context in which businesses operate in 21st century. The shift from production orientation to marketing orientation in twentieth century has continued to consumer orientation epoch in the new millennium. A number of researches have recognized the launching of a successful innovation as a key contributor to create a sustainable demand, as well as to financial and company performance. To build a competitive advantage in high competitive markets many pioneer companies have differentiated themselves by developing innovative products/services. However, studies showed that the failure rate of new-products is very high (ranging from 33% to over 60%) and has not improved over the last decades. Consequently, the extremely high costs associated with the failure of a new product, stresses the importance of a model that can effectively forecast the market penetration of a new product. The acceptance of new product might be affected by several factors. For several years, researchers and marketers have tried to explore the factors that can play role in acceptance or rejection of new products. This study contributes and extends the understanding of the role of religiosity, ethnicity, individual’s values and innovativeness, as personal traits, on acceptance of new products/services in Malaysian context. Seven hundred individuals from urban area of Malaysia were asked to answer the questionnaire. Questionnaires were distributed based on self-administrated method in shopping malls, sports complex, train stations and airports in three different cities of Malaysia. Findings show religiosity and ethnicity have negative relationship with openness to change (stimulation, self-direction and hedonism) and conservation (traditions and conformity). Conservation values have negative effects on consumer innovativeness and acceptance of new products. In contrast, openness to change values show positive relationship with innovativeness and acceptance of new products. Theoretically, the developed model of this study makes an important contribution to the body of consumer behavior literature. Exploring the mechanism through which value affects consumer innovativeness could benefit marketers of companies in determining the target market and in adjusting marketing strategies in each stage of the product life cycle. However, the implications of this research study should be considered in the light of the potential limitations. These might include limitations of sampling method, timem horizon of study and data collection method.